The Effect of Different Types of Manure on the Content of NDF, ADF, Hemicellulose, and Cellulose in Elephant Grass (Pennisetum purpureum) Cv. Taiwan at the First Cutting - Marianos, F; Mega Sari, Rica; Surtina, Dara (Journal of Animal Nutrition and Production Science, 2024)
This research aimed to determine the effect of different types of manure on the NDF, ADF, hemicellulose, and cellulose content of elephant grass (Pennisetum purpureum) cv. Taiwan at the first cutting. The study used 16 polybags and 16 stem cuttings of elephant grass (Pennisetum purpureum) cv. Taiwan has acidic soil with a pH of around 4-4.5 totaling 136 kg, and various types of manure (cow, goat, and chicken) each amounting to 8 kg. The study used a Completely Randomized Design, with 4 treatments and 4 replicates. The results showed that the Neutral Detergent Fiber (NDF) content of elephant grass (Pennisetum purpureum) cv. Taiwan had the highest values of PO (58.73), P1 (57.33), P3 (56.69), and P2 (55.76), while the Acid Detergent Fiber (ADF) content had the highest values of P3 (49.35), P2 (48.04), P1 (47.99), P0 (47.64). The cellulose content had the highest values of P0 (49.87), P1 (48.88), P2 (41.69), P3 (40.69), and the hemicellulose content had the highest values of P0 (9.93), P1 (9.23), P2 (8.63), P3 (7.02). It can be concluded that different types of manure had a significant effect on the NDF, ADF, cellulose, and hemicellulose content of elephant grass (Pennisetum purpureum) cv. Taiwan at the first cutting.